Interdisciplinary collaboration experiences in creating an everyday rehabilitation model: a pilot study - Moe, Aud (J Multidiscip Healthc, 2016)
BACKGROUND: When functional impairment occurs, assistance to achieve self-help can lead to qualitatively more active everyday life for recipients and better use of community resources. Home-based everyday rehabilitation is a new interdisciplinary service for people living at home. Rehabilitation involves meeting the need for interprofessional services, interdisciplinary collaboration, and coordination of services. Everyday rehabilitation is a service that requires close interdisciplinary cooperation. The purpose of this study was to gain knowledge about employees’ experiences with establishing a new multidisciplinary team and developing a team-based work model. METHOD: The study had a qualitative design using two focus group interviews with a newly established rehabilitation team. The sample consisted of an occupational therapist, two care workers with further education in rehabilitation, a nurse, a physiotherapist, and a project leader. Data were analyzed by thematic content analysis. RESULTS: The data highlight three phases: a planning phase (ten meetings over half a year), a startup phase of trials of interdisciplinary everyday rehabilitation in practice (2 months), and a third period specifying and implementing an everyday rehabilitation model (6 months). During these phases, three themes emerged: 1) team creation and design of the service, 2) targeted practical trials, and 3) equality of team members and combining interdisciplinary methods. CONCLUSION: The team provided information about three processes: developing work routines and a revised team-based flow chart, developing team cooperation with integrated Trans- and interdisciplinary collaboration, and working with external exchange. There is more need for secure network solutions.